2016
DOI: 10.1002/prot.25163
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity characterization for eight putative nudix hydrolases. Evaluation of criteria for substrate identification within the Nudix family

Abstract: The nearly 50,000 known Nudix proteins have a diverse array of functions, of which the most extensively studied is the catalyzed hydrolysis of aberrant nucleotide triphosphates. The functions of 171 Nudix proteins have been characterized to some degree, although physiological relevance of the assayed activities has not always been conclusively demonstrated. We investigated substrate specificity for eight structurally characterized Nudix proteins, whose functions were unknown. These proteins were screened for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…2a-h and Additional file 3, respectively). Literature search showed that most of these genes have known functions: tk2 [36] is a deoxyribonucleoside kinase that is required for mitochondrial DNA synthesis; drd3 [37] is dopamine receptor which is associated with cognitive, emotional, and endocrine functions; cldn23 [38] is an integral membrane protein that maintains cell polarity and signal transductions; nudt13 [39] is hydrolase and its function is also largely unknown; itih2 [40] is a serine protease inhibitor that carries hyaluronan in plasma; flvcr1 [41] is a heme transporter that has a critical role in erythropoiesis by protecting developing erythroid cells from heme toxicity; pomt1 [42] is an O-mannosyltransferase that is a component of many polysaccharides and glycoproteins; prkcq [43] is a serine- and threonine-specific protein kinase that is important for T-cell activation; and otulina [44] is a predicted deubiquitinase also called fam105ba . qPCR confirmed the differential expression of these genes in bad quality eggs relative to good quality eggs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2a-h and Additional file 3, respectively). Literature search showed that most of these genes have known functions: tk2 [36] is a deoxyribonucleoside kinase that is required for mitochondrial DNA synthesis; drd3 [37] is dopamine receptor which is associated with cognitive, emotional, and endocrine functions; cldn23 [38] is an integral membrane protein that maintains cell polarity and signal transductions; nudt13 [39] is hydrolase and its function is also largely unknown; itih2 [40] is a serine protease inhibitor that carries hyaluronan in plasma; flvcr1 [41] is a heme transporter that has a critical role in erythropoiesis by protecting developing erythroid cells from heme toxicity; pomt1 [42] is an O-mannosyltransferase that is a component of many polysaccharides and glycoproteins; prkcq [43] is a serine- and threonine-specific protein kinase that is important for T-cell activation; and otulina [44] is a predicted deubiquitinase also called fam105ba . qPCR confirmed the differential expression of these genes in bad quality eggs relative to good quality eggs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Within this category, k cat / K m values, when available, usually provided the most informative conclusion, and thus were assigned with the highest confidence scores. High k cat / K m values (e.g., >10 6 M −1 s −1 ) serve as a sufficient condition to indicate likely physiological substrates, while observation of low k cat / K m values for Nudix hydrolases often means the investigated chemical is not likely the physiological substrate for the enzyme . Hence, we assigned scores of 0.99, 0.85, 0.5, 0.2, and 0.1, corresponding to k cat / K m values 10 7 , 10 6 , 10 5 , 10 4 , 10 3 M −1 s −1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Similar NUDIX hydrolase family proteins act on the di-and tri-phosphate versions of other types of damaged DNA and RNA nucleosides, including 8-oxoadenosine, 2-hydroxyadenosine, and 5-hydroxycytosine. 30,32 NUDIX hydrolase family proteins also act on many other nucleotide-containing compounds, such as the enzyme cofactors NADH and TPP, the signaling molecule Ap4A, and the adenylated sugar ADP-glucose. 30,32,33 Some NUDIX hydrolases display broad substrate specificity and act on a range of nucleoside di- and triphosphates.…”
Section: Resultsmentioning
confidence: 99%
“…30,32 NUDIX hydrolase family proteins also act on many other nucleotide-containing compounds, such as the enzyme cofactors NADH and TPP, the signaling molecule Ap4A, and the adenylated sugar ADP-glucose. 30,32,33 Some NUDIX hydrolases display broad substrate specificity and act on a range of nucleoside di- and triphosphates. In general, NUDIX hydrolases are considered to be “housekeeping” enzymes that maintain a balance between various nucleotide pools.…”
Section: Resultsmentioning
confidence: 99%